Increased Network Inhibition in the Dentate Gyrus of Adult Neuroligin-4 Knock-Out Mice - Muellerleile, Julia; Vnencak, Matej; Sethi, Mohammad Valeed Ahmed; Jungenitz, Tassilo; Schwarzacher, Stephan W.; Jedlicka, Peter; Justus Liebig University Giessen (My University, 2023)
Loss-of-function mutations in neuroligin-4 (Nlgn4), a member of the neuroligin family of postsynaptic adhesion proteins, cause autism spectrum disorder in humans. Nlgn4 knockout (KO) in mice leads to social behavior deficits and complex alterations of synaptic inhibition or excitation, depending on the brain region. In the present work, we comprehensively analyzed synaptic function and plasticity at the cellular and network levels in hippocampal dentate gyrus of Nlgn4 KO mice. Compared with wild-type littermates, adult Nlgn4 KO mice exhibited increased paired-pulse inhibition of dentate granule cell population spikes, but no impairments in excitatory synaptic transmission or short-term and long-term plasticity in vivo. In vitro patch-clamp recordings in neonatal organotypic entorhino-hippocampal slice cultures from Nlgn4 KO and wild-type littermates revealed no significant differences in excitatory or inhibitory synaptic transmission, homeostatic synaptic plasticity, and passive electrotonic properties in dentate granule cells, suggesting that the increased inhibition in vivo is the result of altered network activity in the adult Nlgn4 KO. A comparison with prior studies on Nlgn 1–3 knockout mice reveals that each of the four neuroligins exerts a characteristic effect on both intrinsic cellular and network activity in the dentate gyrus in vivo.
Keywords: dentate granule cell; in vivo electrophysiology; organotypic slice culture; paired-pulse inhibition; synaptic scaling; whole-cell patch-clamp recording; ddc:610